2019
DOI: 10.1364/boe.10.002932
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal effect by 808-nm laser irradiation of melanin: a proof-of-concept study of photothermal therapy using B16-F10 melanotic melanoma growing in BALB/c mice

Abstract: The photothermal effect is undergoing great interest due to advances in new photosensitizing materials and better-suited light sources, but studies are frequently hampered by the need to employ exogenous photothermal agents and expensive irradiation devices. Here we present a simple strategy based on direct NIR irradiation of the melanin pigment with a commercial 808-nm laser pointer. Proof-of-concept studies showed efficient photothermal effects on melanin in vitro and in vivo. After NIR irradiation, BALB/c m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Eumelanin is practically the ideal photothermal sensitizer, and the massive vibrational decay from photo-excited electrons in melanotic melanomas induces an efficient heating response that results in coagulative necrosis of the tumor (Kostenich et al, 2000;Colombo et al, 2019;Blázquez-Castro and Stockert, 2021). In the case of melanin-PTT, the endogenous chromophore eumelanin is the selective PTT agent for NIR irradiation (Fig.…”
Section: Photothermal Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Eumelanin is practically the ideal photothermal sensitizer, and the massive vibrational decay from photo-excited electrons in melanotic melanomas induces an efficient heating response that results in coagulative necrosis of the tumor (Kostenich et al, 2000;Colombo et al, 2019;Blázquez-Castro and Stockert, 2021). In the case of melanin-PTT, the endogenous chromophore eumelanin is the selective PTT agent for NIR irradiation (Fig.…”
Section: Photothermal Therapymentioning
confidence: 99%
“…Ignition of blotted papers occurs after few seconds, when temperature reaches 218-246°C, and it is a clear end point of the photothermal reaction. The temperature increase of aqueous solutions of photothermal candidates subjected to irradiation can be also recorded by using a simple mercury thermometer or a thermocouple to assess photothermal responses (Blázquez-Castro et al, 2018;Colombo et al, 2019). Useful biological materials to study mechanisms and applications of melanin-based PTT include bacterial biofilms, 3D melanoma spheroids, and whole organisms such as black amphibian eggs and embryos (Rhinella, Bufo), black insects (Aedes aegipty), plant beans (Phaseolus vulgaris), and black seeds (Sesamum indicum, Salvia hispanica, etc.…”
Section: Photothermal Therapymentioning
confidence: 99%
“…As mentioned, sepiomelanin, isolated from the ink sac of cuttlefish, is considered to be an easily accessible analogous of eumelanin of mammals. Moreover it exhibits a very rapid and strong photothermal response upon NIR-irradiation [ 166 ], and an enhanced photothermal efficiency with respect to artificial melanin-like PDA NPs [ 167 ]. In the light of this, Wang et al took advantage of melanin extracted from ink of sacrificed cuttlefish for the construction of Au-decorated melanin (Au-M) nanocomposites [ 168 ].…”
Section: Mnp Based Therapy and Theranosticsmentioning
confidence: 99%
“…One of the promising strategies to improve the anti-tumor immune responses is the vaccination with whole tumor antigens derived from whole cell lysates. In addition to whole tumor antigens, the whole cell lysates possess melanin that can as a photosensitizer for heat generation and subsequent PTT of cancer [125]. As an example, Ye et al reported the design and fabrication of a transdermal cancer vaccine MN patch based on cross-linked HA materials [126].…”
Section: Mns For Effective Delivery Of Other Cancer Vaccinesmentioning
confidence: 99%